KIF3C Promotes Proliferation, Migration, and Invasion of Glioma Cells by Activating the PI3K/AKT Pathway and Inducing EMT - Gao, Yang (Biomed Res Int, 2020)
Kinesin superfamily protein 3C (KIF3C), a motor protein of the kinesin superfamily, is expressed in the central nervous system (CNS). Recently, several studies have suggested that KIF3C may act as a potential therapeutic target in solid tumors. However, the exact function and possible mechanism of the motor protein KIF3C in glioma remain unclear. In this study, a variety of tests including CCK-8, migration, invasion, and flow cytometry assays, and western blot were conducted to explore the role of KIF3C in glioma cell lines (U87 and U251). We found that overexpression of KIF3C in glioma cell lines promoted cell proliferation, migration, and invasion and suppressed apoptosis, while silencing of KIF3C reversed these effects. Ectopic KIF3C also increased the expression of N-cadherin, vimentin, snail, and slug to promote the epithelial-mesenchymal transition (EMT). Mechanistically, overexpression of KIF3C increased the levels of phosphatidylinositol 3-kinase (PI3K) and phosphorylated protein kinase B (p-AKT). These responses were reversed by KIF3C downregulation or AKT inhibition. Our results indicate that KIF3C promotes proliferation, migration, and invasion and inhibits apoptosis in glioma cells, possibly by activating the PI3K/AKT pathway in vitro. KIF3C might act as a potential biomarker or therapeutic target for further basic research or clinical management of glioma.